Ploidy determination in Musa germplasm using pollen and chloroplast characteristics - Tenkouano, A.; Crouch, J.H.; Crouch, H.K.; Vuylsteke, D.R. (1998)
We attempted to determine ploidy level in the gametophyte and the sporophyte of Musa using pollen and chloroplast characteristics, respectively. In the gametophyte, interploidy differences accounted for 63.8 % of the genetic variance for pollen diameter and 87.5% for pollen stainability, the remainder being attributable to intraploidy differences among clones. While pollen count and stainability effectively separated triploid accessions from diploids or tetraploids, they did not discriminate between diploids and tetraploids. In the sporophyte, the relative contributions of interploidy and intraploidy differences to genetic variation in the number of chloroplasts in stomatal guard cells were 70.8% and 29.2%, respectively. Although pollen diameter and chloroplast number increased with ploidy, the use of the sporophytic parameter appears to provide a more satisfactory means of estimating ploidy status in Musa.